Cultivation of Microalgae Spirulina platensis in Palm Oil Mill Effluent (POME) Media with Variations of POME Concentration and Nutrient Composition - Fitria Yuli Anggita Sari; I Made Aditya Suryajaya; Marcelinus Christwardana; H. Hadiyanto (Diponegoro University, 2022)
Indonesia and Malaysia are recognized as the world's leading producers of palm oil. Along with the growth of the palm oil industry in Indonesia, the amount of Palm Oil Mill Effluent has increased. Palm Oil Mill Effluent (POME) is a liquid byproduct of the palm oil production process. POME has been treated using aerobic and anaerobic ponds to lower Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) levels, but it still includes nutrients like as C,N,P that are beneficial to the development of microalgae. On this study, Spirulina platensis was grown in POME medium with 20%, 40%, and 60% V. concentrations. Every two days, the nutrients Urea, NaHCO3, and TSP were administered. Seven days of aeration and 24-hour lights are used throughout the cultivation phase. The results indicate that POME with a 20 % concentration is the optimal medium for plant growth. Add 25 ppm Urea, 50 ppm TSP, and 200 ppm NaHCO3 for the optimal nutritional composition. At the same treatment on various medium, the highest growth rate of Spirulina platensis is determined to be µ = 0.128% per day, with an optical density of 0.648. Carbon reductions range from 83.03 % to 84.10 %, while Nitrogen savings range from 78 % to 79.55 % when POME is used as a growing medium. This study also shown that the C, N, and P concentrations of POME fall by 93 to 98 %, 99 to 99.5 %, and 92 to 97 %, respectively.